The Term Ma'shiyah in the Qur'an and Its Relevance in the Digital Era - Maemunah, St.; Yusuf, Muhammad; Haddade, Hasyim (Manunggal Halim Jaya, 2025)
This study aimed to analyze the term ma'shiyah in the Qur'an and its relevance in the digital era using the thematic interpretation approach from Al-Farmawi's perspective. The focus was on how the concept of ma'shiyah, which refers to disobedience to Allah's commands, remains pertinent to actions in the digital world, such as cyberbullying, spreading slander, and disseminating hoaxes. The research employed a literature study with a thematic interpretation approach, analyzing various Qur'anic verses containing the term ma'shiyah based on the interpretations of scholars, particularly Al-Farmawi. The findings revealed that the term ma'shiyah appears in 23 Surahs, with several derivations conveying interrelated meanings. Moreover, the concept of ma'shiyah in the Qur'an was linked to social violations in the digital era, such as cyberbullying. As a foundational principle of ethics in digital interactions, the concept of ma'shiyah highlights the importance of upholding honesty, dignity, and justice in accordance with Islamic teachings.